A Human Hematopoietic Niche Model Supporting Hematopoietic Stem and Progenitor Cells In Vitro. Issue 10 (3rd April 2019) - Braham, Maaike V. J.; Li Yim, Amélie S. P.; Garcia Mateos, Jara; Minnema, Monique C.; Dhert, Wouter J. A.; Öner, F. Cumhur; Robin, Catherine; Alblas, Jacqueline
Abstract: Niches in the bone marrow regulate hematopoietic stem and progenitor cell (HSPC) fate and behavior through cell–cell interactions and soluble factor secretion. The niche‐HSPC crosstalk is a very complex process not completely elucidated yet. To aid further investigation of this crosstalk, a functional in vitro 3D model that closely represents the main supportive compartments of the bone marrow is developed. Different combinations of human stromal cells and hydrogels are tested for their potential to maintain CD34 + HSPCs. Cell viability, clonogenic hematopoietic potential, and surface marker expression are assessed over time. Optimal HSPC support is obtained in presence of adipogenic and osteogenic cells, together with progenitor derived endothelial cells. When cultured in a bioactive hydrogel, the supportive cells self‐assemble into a hypoxic stromal network, stimulating CD34 + CD38 + cell formation, while maintaining the pool of CD34 + 38 − HSPCs. HSPC clusters colocalize with the stromal networks, in close proximity to sinusoidal clusters of CD31 + endothelial cells. Importantly, the primary in vitro niche model supports HSPCs with no cytokine addition. Overall, the engineered primary 3D bone marrow environment provides an easy and reliable model to further investigate interactions between HSPCs and their endosteal and perivascular niches, in the context of normal hematopoiesis or blood‐related diseases. Abstract : A human hematopoietic niche model is developed, supporting hematopoietic stem and progenitor cells (HSPCs) in vitro, without cytokine supplementation. The cocultured primary cells (mesenchymal stromal cells, endothelial progenitor cells, adipogenic stromal cells, or osteogenic stromal cells) support HSPCs in a 3D microtissue. The supportive environment is characterized in terms of hypoxia, cell–cell interactions, and localization.